Improvement of capacity fading resistance of LiMn2O4 by amphoteric oxides - Park, Sung Bin; Shin, Ho Chul; Lee, Wan-Gyu; Cho, Won Il; Jang, Ho (ELSEVIER, 2008)
The capacity fading of LiMn2O4 is improved by adding amphoteric oxides such as Al2O3, ZnO, SnO2, and ZrO2 to the cathode slurry. The effectiveness of the amphoteric oxides on the fade resistance of LiMn2O4 is compared by measuring the capability of scavenging hydrofluoric acid (HF) in the electrolyte by the oxides using a pH meter and by BET surface analysis. Results suggest that the capacity fading is determined by the reactivity of oxides with HF and the effective surface-area of the oxide particles when they were mixed in the slurry. Zinc oxide is the most effective of the oxides in scavenging HF. (C) 2008 Elsevier B.V All rights reserved.
Keywords: SPINEL; ELECTRODES; CATHODE; PERFORMANCE; CO